Comprehensive study on optical and luminescence properties of Sm3+ doped magnesium borotellurite glasses - Zalamin, Siti Norul Fadhilah; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Abdul Karim, Muhammad Khalis; Mohamad Yamin, Nurul Afiqah; Ismail, Nur Atikah Nazihah (Elsevier, 2022)
This research reports the optical and luminescence properties of new tellurite glass system with nominal composition of x(Sm2O3)–10MgO–30B2O3−(60−x)TeO2, where x = 0, 0.5, 1.0, 2.0 and 3.0 mol% synthesized via fast cooling melt-quenching method. The physical characteristic, UV–visible, refractive index, and photoluminescence spectroscopy techniques were used to examine the structural changes and optical performance of the glasses. No sharp peak appeared in the diffraction of XRD region proved the amorphous state of the glasses. The bulk density of the prepared glass samples presented an increasing trend from 4.105 to 4.403 g/cm3 meanwhile the molar volume showed opposite pattern with range value of 28.69–29.39 cm3/mol. The highest density governed by glass sample with concentration of samarium ions at 3.0 mol%, which is 4.403 g/cm3. The optical absorption spectra were characterized to determine the energy band gap, Urbach energy, and refractive index of the glasses. The obtained values for refractive index is in between 2.481 and 2.575 meanwhile for Urbach energy is 0.238–0.319 eV. The optical absorption spectra reveal eleven energy transitions bands centered at 4G9/2, 4I11/2, 4F3/2, 4G5/2, 6F11/2, 6F9/2, 6F7/2, 6F5/2, 6F3/2, 6H15/2, 6F1/2 from ground state of 6H5/2. Four strong emission peaks occurred in photoluminescence, with the highest red emission peak at 600 nm. Chromaticity coordinates of the glass samples were determined as well as the dominant wavelength and colour purity, using CIE Chromaticity diagram 1931.